We are captives to digital media surveillance Netizens awareness and perception of social media surveillance - Oguafor, Ifeanyichukwu Valerie; Nevzat, Raziye (Sage Publications Ltd, 2025)
With the increasing use of social media and the frequent question of privacy invasion, this study aims to give an insight into young adult netizen's-citizens of the internet and people born into the digital era- perception of the existing surveillance culture surrounding social media today as studies and recent statistics have shown that young adults all over the world make up the greater percentage of social media users. While this paper is centered around privacy on social media and information capitalism as key theoretical frameworks that conceptualizes surveillance and participatory surveillance system, this study gives an exploratory understanding of netizens opinion on the issue as we investigate their awareness and perception of social media surveillance. Using a qualitative method, this study utilizes interviews with 35 university students between the ages of 18-25 as a primary source of data collection. Findings from this study show although netizens are aware of the surveillance culture on social media, they strongly believe that they are captives of social media surveillance. Participatory surveillance occurs amongst them only because they have little or no choice as surveillance is embedded in the digital world they choose to participate in. Lastly, participants believe that it is difficult to hold a faceless watcher accountable so they do not question the system.
Keywords: information capitalism; netizens; surveillance; participatory surveillance; privacy; social media